Platelet activation at the onset of human endotoxemia is undetectable in vivo. (3rd July 2016) - Schrottmaier, Waltraud Cornelia; Kral, Julia Barbara; Zeitlinger, Markus; Salzmann, Manuel; Jilma, Bernd; Assinger, Alice
Abstract: Infection induces platelet activation and consumption, which leads to thrombocytopenia, enhances microvascular thrombosis, impairs microcirculation and eventually triggers disseminated intravascular coagulation (DIC). It is well characterized that endotoxemia results in a pro-inflammatory and pro-coagulatory state, which favors platelet activation. However the early, direct effects of endotoxemia on platelets have not been investigated so far. Therefore we aimed to determine the early effects of the endotoxin lipopolysaccharide (LPS) on platelet function in vivo . In a human endotoxemia model, 15 healthy volunteers were stimulated with LPS (2 ng/kg). Blood was drawn before, 10, 30 and 60 min after LPS challenge and platelet activation analyzed by flow cytometry (GPIIb/IIIa activation, surface CD62P and CD40L, intraplatelet reactive oxygen formation and platelet–leukocyte aggregates) and ELISA (sCD40L, sCD62P and CXCL4). In parallel, blood samples and platelets were spiked with LPS (50 pg/ml) in vitro and monitored over 60 min for the same platelet activation markers. In vitro platelet stimulation with LPS activated platelets independent of the presence of leukocytes and enhanced their adhesion to endothelial cells. In contrast, in vivo no increase in GPIIb/IIIa activation or surface expression of CD62P was observed. However, endotoxemia resulted in a significant drop in platelet count and elevated the plasma CXCL4 levels already 10 min after the LPS challenge. These data indicate that LPS rapidly activates platelets, leading to α-granule release and endothelial adhesion. This might explain the drop in platelet count observed at the onset of endotoxemia.